Perancangan Aplikasi Point Of Sales (POS) Pada PT. Mutiara Primarasa Abadi Jambi - Mourren Yang, Louis; Hendri; Ibnu Sani Wijaya (Jurnal Informatika Dan Rekayasa Komputer(JAKAKOM), 2025)
Mutiara Primarasa Abadi Jambi is a business engaged in bread sales in Jambi City. Currently, its operational processes still rely on manual record-keeping using books and calculators, leading to several issues. These include lengthy report generation due to the need to manually summarize product entry and sales transactions, inaccuracies in inventory records caused by miscalculations of incoming and outgoing data, and potential errors in sales receipts that could result in financial losses for the company. Additionally, difficulties in monitoring the due dates of receivables that need to be collected from customers further complicate operations. As a solution, a point-of-sales application was designed using PHP as the programming language and MySQL as the database management system. The system development followed the waterfall method and applied a Unified Modeling Language (UML) approach, including use case diagrams, activity diagrams, class diagrams, and flowchart diagrams. The developed system generates structured outputs such as supplier data, product data, customer data, as well as product entry and sales transaction records. Moreover, the system provides the necessary reports to facilitate PT. Mutiara Primarasa Abadi Jambi in managing data more efficiently.